The Relationship between Sea Surface Temperature and Chlorophyll-a Concentration on Mackerel Fish (Rastrelliger kanagurta, Cuvier 1816) Catch Results on Sea Waters of Bengkulu City - Ramadanti, Dhea; Nurdin, Jabang; Maliza, Rita (Jurnal Biologi Tropis, 2025)
This study investigates the relationship between sea surface temperature (SST) and chlorophyll-a concentration in relation to the catch results of mackerel fish (Rastrelliger kanagurta) in Pulau Tikus Beach, Bengkulu City. Remote sensing data from the Aqua MODIS satellite sensor were analyzed over a 12-month period (May-April 2025) to assess monthly fluctuations in SST and chlorophyll-a as indicators of marine productivity. SST values ranged from 28.9°C to 31.2°C, matching the optimal thermal range for mackerel spawning. Chlorophyll-a concentrations ranged from 0.5 to 3.4 mg/m³, indicating a high abundance of phytoplankton and biologically fertile waters. Fishing coordinate data showed that the highest mackerel catches occurred around Pulau Tikus, with Robin-type boats operating approximately 7-8 nautical miles offshore. The relationship between SST and chlorophyll-a revealed that increasing SST was associated with elevated chlorophyll-a levels at depths of 8-15 meters, thereby increasing the probability of mackerel presence.